OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT, TEAMWORK, AND BURNOUT OF NURSES IN SELECTED GOVERNMENT HOSPITALS IN NORTHERN GHANA - Mbemah, Aminu; Sausa, Lualhati; Lopez, Glenda Joy; Marticio, Flor Villa; Orbon, Myrtle (11th International Scholars Conference, 2016)
This study explored the relationship between occupational health and safety management, teamwork, and burnout of 321 nurses in five selected government hospitals in Northern Ghana. The majority (72%) of the respondents were female, married (50%), and with age ranged between 21-39 years old (88%). The descriptive statistics findings showed that the hospital’s occupational health and safety management in terms of policy, planning, implementation, evaluation, improvement and integration of the health and safety practices was perceived by the respondents to be somewhat effective. The level of teamwork in terms of team leadership, mutual performance monitoring, backup behavior and team orientation among the nurse's team was also perceived to be effective. It also revealed the degree of burnout in terms emotional exhaustion, depersonalization, and inefficacy to be at a low level. Regression analysis showed that integration as one dimension of occupational health and safety management significantly predict burnout in terms of emotional exhaustion and only backup behavior significantly influence burnout in terms of emotional exhaustion. The study also revealed that none of the variables predicted depersonalization but recorded team orientation, integration, and length of work experience significantly predict inefficacy. Furthermore, team orientation which accounted for 11.6% of the total variance to be the highest predictor of inefficacy. The result also confirmed other studies that revealed no significant difference between burnout and demographic variables such as; age, marital status, the level of education, and length of working experience, except for gender and unit of assignment which recorded a significant difference in burnout in terms of emotional exhaustion and inefficacy, respectively. This result supports the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) theory.